2015
DOI: 10.3390/ijerph120404354
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Benefits of Long-Term Exposure to Residential Green and Blue Spaces: A Systematic Review

Abstract: Many studies conducted during the last decade suggest the mental health benefits of green and blue spaces. We aimed to systematically review the available literature on the long-term mental health benefits of residential green and blue spaces by including studies that used standardized tools or objective measures of both the exposures and the outcomes of interest. We followed the PRISMA statement guidelines for reporting systematic reviews and meta-analysis. In total 28 studies were included in the systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

36
573
1
16

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 866 publications
(690 citation statements)
references
References 65 publications
(161 reference statements)
36
573
1
16
Order By: Relevance
“…These benefits are classified as ecosystem services (ES) [10], the most important in urban areas being the cultural ES which are essential for the well-being and health of the citizens [11][12][13][14][15][16], while at the same time being commonly underestimated due to difficulties in quantification [17]. Potential benefits from green infrastructure and the possibility of outdoor recreational activities are limited in many cities due to the low occurrence of good quality green space [18,19] and variations in people s preferences [20].…”
Section: Introductionmentioning
confidence: 99%
“…These benefits are classified as ecosystem services (ES) [10], the most important in urban areas being the cultural ES which are essential for the well-being and health of the citizens [11][12][13][14][15][16], while at the same time being commonly underestimated due to difficulties in quantification [17]. Potential benefits from green infrastructure and the possibility of outdoor recreational activities are limited in many cities due to the low occurrence of good quality green space [18,19] and variations in people s preferences [20].…”
Section: Introductionmentioning
confidence: 99%
“…Psychological studies highlight that direct contact with nature is crucial for human well-being and psycho-physical development in a long term perspective. It is even accepted that the presence of green areas affects life expectancy [11,13,14,16]. Thus, green infrastructure can become the infrastructure of a healthy life, and are most needed in city centers, densely built-up areas or highly populated areas.…”
Section: Discussionmentioning
confidence: 99%
“…These benefits, classified as cultural ecosystem services [10], can often be regarded as the most important services in urban areas for the citizens well-being and health [11][12][13][14][15][16], while being at the same time commonly underestimated due to difficulties in quantification [17]. Potential benefits from green infrastructure and the possibility of outdoor recreational activities are limited in many cities due to the low occurrence of good quality green space [18][19] and variations in people′s preferences [20].…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of GIS buffer analyses considers other health outcomes and may help explain how distance within which greenness is measured influences health. For instance, at least three articles have tied academic achievement to school greenness [17][18][19], and another thirteen articles have tied mental health to residential greenness [9] with buffer analyses. Albeit, the mechanisms by which greenness improves these outcomes may be different than those by which greenness improves physical health.…”
Section: Discussionmentioning
confidence: 99%
“…To identify possible criteria that would demonstrate potential bias, we consulted criteria used in prior systematic literature reviews on greenness and human health outcomes [9,10]. We found that some prior criteria (i.e., multiplicity of outcome variables within a single article) did not apply to our unit of examination -that is, analyses rather than articles -and other criteria represented characteristics of potential bias which we had already excluded in our screening process (i.e., expert assessments of "greenness" versus land-cover maps or satellite system assessments).…”
Section: Evaluation Of Possible Biasmentioning
confidence: 99%